P65 Prognostic non-invasive biomarkers for all-cause mortality in non-alcoholic fatty liver disease: systematic review and meta-analysis. (19th June 2022) - Cianci, Nicole; Subhani, Mohsan; Hill, Trevor; Khanna, Amardeep; Zheng, Dong; Sheth, Abhishek; Crooks, Colin; Aithal, Guruprasad
Abstract : Introduction: Non-alcoholic fatty liver disease (NAFLD) represents a growing public health concern, with patients having higher risk of morbidity and mortality. The aim of this systematic review was to evaluate available evidence on the use of non-invasive test(s) as prognostic factors for mortality in NAFLD. Methods: We performed electronic searches of Medline and Embase (Ovid) until 7 th January 2021 of studies in NAFLD populations. Prognostic markers included serum biomarkers, non-invasive scoring systems, and non-invasive imaging. Outcomes included all-cause, and cause-specific mortality. We conducted a systematic review and a meta-analysis of non-invasive scoring systems for predicting all-cause and cardiovascular mortality, calculating pooled hazard ratios and 95% confidence (STATA 16.1). Results: Searches identified 2850 studies – 24 were included. 16 studies reported non-invasive scoring systems, 10 studies reported individual biomarkers, and 1 study reported imaging modalities. 4 studies (6, 324 participants) had data available for inclusion in the analysis. The non-invasive scoring system that performed best at predicting all-cause mortality was NFS [pHR 3.07 (1.62-5.83)], followed by FIB4 [pHR 3.06 (1.54-6.07)], BARD [pHR 2.87 (1.27-6.46)], and APRI [pHR 1.90 (1.32-2.73)]. NFS was also associated with cardiovascular-related mortality [pHR 3.09 (1.78-5.34)]. Conclusions: This study reaffirms that non-invasive scoring systems, especially NFS, is a reliable prognostic marker of all-cause mortality in NAFLD patients. We further report that NFS can be used specifically to predict cardiovascular-related mortality. Our systematic review has highlighted several other non-invasive prognostic markers for mortality in NAFLD. These findings can inform clinical practice in risk stratifying and targeting NAFLD patients.